Genomic epidemiology of Candida auris in a general hospital in Shenyang, China: a three-year surveillance study. Issue 1 (1st January 2021) - Tian, Sufei; Bing, Jian; Chu, Yunzhuo; Chen, Jingjing; Cheng, Shitong; Wang, Qihui; Zhang, Jingping; Ma, Xiaochun; Zhou, Baosen; Liu, Ling; Huang, Guanghua; Shang, Hong
ABSTRACT: Candida auris is an emerging pathogenic fungal species found worldwide. Since April 2016, C. auris colonization/infection cases have been found in a general hospital in Shenyang, China. The genome-based phylogenetic studies of these isolates remain undefined. In the current study, the microbiological characteristics and antifungal susceptibility of these C. auris isolates, which were collected in Shenyang during the three-year period (2016–2018), were investigated. Whole-genome sequencing was applied to investigate the genetic variation and molecular epidemiological characteristics. A total of 93 C. auris isolates, including 92 clinical isolates and 1 environmental screening isolate were identified. Among the investigated wards, the C. auris cases were the most prevalent (97.4%, 37/38) in four intensive care units (ICUs). The Shenyang isolates carrying the VF125AL mutation in the key drug-resistance gene ERG11 were mainly fluconazole resistant and formed a distinct subclade under the South African clade according to the phylogenetic and population structural analyses. In addition, the Shenyang subclade was found to be closely related to the British subclade in the aspect of genetic distance. As a conclusion, this study provides an important clue for revealing the origin of C. auris found in Shenyang and could also contribute to improve the understanding of the epidemiological characteristics of C. auris worldwide.